Empowering the PKK Cadres as a Waste Bank Agent in Waste Management Efforts to Keep Environmental Health - Ni Putu Emy Darma Yanti; Kadek Cahya Utami; Indah Mei Rahajeng; Gusti Ayu Ary Antari (Global Health Science Group, 2020)
Waste management that needs to be carried out comprehensively and integratedly from the downstream flow in order to provide economic benefits, be healthy for the community, safe for the environment and can change people's behavior. Tista Village already has a Garbage Bank which is headquartered at the Village Office, but it has not been utilized properly by the community. The purpose of this community service activity is knowledge and attitudes regarding PKK waste management as a waste bank agent and the implementation of the Waste Bank program in Tista Village. The community service activity carried out was to provide training on the implementation of the waste bank with the method of lectures, discussions, demonstration, and focus group discussions attended by 35 PKK cadres. Methods of using data using a questionnaire given before and after training. Data analysis used the Wilcoxon test with a confidence level of 95%. The results of the community service activities received an increase in the knowledge and attitude of PKK cadres as Garbage Bank agents about proper waste management after being given training.